A importância da simetria de informações para o sucesso dos projetos de tecnologia da informação, por meio das ações de cooperação - Oliveira, Henrique Pontes Gonçalves de (2017)
With the advancement of technological solutions and a business environment increasingly agile and competitive, the Information Technology area has, growingly, assumed an essential part in organizations. As a result, the number of IT demands has increased significantly, making the usage of project management practices a fundamental component in meeting these demands. In Information Technology projects the generation and flow of information, as well the interaction between the areas associated with the projects, is significantly high, requiring adequate communication procedures, which are the most sensitive and extremely associated to the success or failure of the project. This research explored, through a multiple case study, the influence of information symmetry, that is, the adequate distribution of project information among its stakeholders through cooperation actions in the projects’ success. After an extensive review of the literature on IT projects, project management, information symmetry and cooperation, three propositions were developed in order to answer the research question. The first proposes that the symmetry of information in IT projects facilitates cooperation actions; the second, that cooperation actions influence the success of IT projects, and the third, that efficient communication and symmetry of information, referring to IT projects, through cooperation actions, are essential factors for the success of the project. The research data collection stage was carried out in two large multinational companies, in the retail sector, in the food and garments segments and, in each of them, qualitatively analyzed a strategic project for the company. In the two analyzed projects, it was verified that did not obtain satisfactory results, although their products were delivered. The main factors pointed out were problems in the communication process, mainly the information symmetry. It was still verified that the inefficiency in the communication directly harms the cooperation actions and proved that the inadequate distribution of information is a preponderant factor for the generation of conflicts and, consequently, the failure of the project. However, it was pointed out by all interviewees, in both projects, that information symmetry influences cooperation actions between teams and, it is essential to achieve the success of IT projects.